Thermal analysis of ferromagnet actuator by finite element method - OYMAN SERTELLER, NECİBE FÜSUN (ELSEVIER SCIENCE BV, 2006)
In this study a standard type contactor is considered as an actuator and its thermal analysis is given. The coil operates as a heat source, and the heat conduction on the ferromagnetic body is investigated. The copper and ferrite losses are ignored and the temperature distribution in the ferromagnetic core is evaluated under stationary condition. FL 150 D standard type contactor is considered for two-dimensional heat conduction problem by using the finite element method (FEM). The numerical results have been compared with the results of the boundary element method (BEM). Three different widely used materials have been examined in the analysis. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: contactor; ferromagnetic material; thermal analysis; finite element method